Side effects among healthcare workers from a large Milan university hospital after second dose of BNT162b2 mRNA COVID-19 vaccine - Borroni, Elisa; Consonni, Dario; Cugno, Massimo; Lombardi, Andrea; Mangioni, Davide; Bono, Patrizia; Oggioni, Massimo; Uceda Renteria, Sara; Bordini, Lorenzo; Nava, Carlo Domenico; Letzgus, Matteo; Gentiloni Silverj, Flaminia; et al. (La Medicina del Lavoro, 2021)
Background: In Italy, healthcare workers (HCWs) were among the first to receive COVID-19 vaccination. Aim of the present study is to evaluate frequency and severity of adverse events (AEs) following the second dose of BNT162b2 vaccine among HCWs of a large university hospital in Milan, Italy. Methods: One month after having received the second dose of vaccine, HCWs filled-in a form about type, severity, and duration of post-vaccination local and systemic symptoms. We calculated the overall frequency of AEs and used multivariable Poisson regression models (adjusted for sex, age, BMI, smoking, allergy history, previous SARS-CoV-2 infection, anti-hypertensive therapy, and occupation) to calculate risk ratios (RR) and 95% confidence intervals (CI) of AEs according to selected variables. Results: We included 3659 HCWs. Overall, 2801 (76.6%) experienced at least one local event, with pain at injection site being the most frequent (2788, 76.2%). Systemic events were reported by 2080 (56.8%) HCWs, with fatigue (52.3%), muscle pain (42.2%), headache (37.7%), joint pain (31.9%), and fever (26.2%) being the most frequent. Risks of systemic events were associated with female gender (RR=1.14, CI: 1.06-1.23), age (strong decrease with increasing age, p-trend<0.001), allergy history (RR=1.13, CI: 1.05-1.20), and current smoking (RR=0.90, CI: 0.84-0.97). HCWs with previous SARS-CoV-2 infection (even if symptomatic) were not at increased risk. Conclusions: Both local and systemic acute effects after second dose of BNT162b2 vaccine were frequently reported. However, symptoms were mostly light/mild and of short duration. Thus, our findings support the safety of COVID-19 vaccination in adults in relatively good health.